Representações sociais do processo de viver e envelhecer pelo exercício de leitura e escrita : a participação do sujeito idoso em uma oficina literária - Borowski, Pia Elena Zancanaro (2014)
Elderly people, when going through an experience, elaborate social representations of their process of living and aging, since it is something intrinsic to the group they belong. In this study we sought to understand the meaning of living and aging of elderly individuals through practices of reading and writing, focusing on their participation in a literary workshop. With such restriction, we aimed to investigate what are the social representations in this process of discursive activities, and the meanings it assigns for living and aging. We also assessed the effects of this practice on social inclusion of older people, and how these images of aging have become more significant in this context. Based on the Theory of Social Representations, whereas the researched problem focuses on human experiences, values, and beliefs as part of social reality, the work was configured as a case study research, assuming an observational character with a qualitative approach, and taking as participants 15 elderly people, aged between 60 and 78 years, who attend the Literary Workshop of the Regional Centre of Studies and Activities for the Elderly, at the University of Passo Fundo, RS, Brazil. We investigated the assumption that the participation of the elderly individual in a literary workshop, which is a facilitator for the construction of interesting images, may represent social reintegration, recovery of citizenship by promoting the practice of oral communication, reading, and writing, as relationships tools. The main findings show that elderly individuals express as human beings, share and broaden their accumulated knowledge, their cultural baggage of the relation to the universe they live in, having the ability to transform themselves, in other words, the ability to be transformation agents. Such exercises reflect the intent of the space proposed in the workshop, which proved to be the promoter of expression in maturity, aging or old age